2015
DOI: 10.7205/milmed-d-14-00536
|View full text |Cite
|
Sign up to set email alerts
|

Veterans' Perspectives on Benefits and Drawbacks of Peer Support for Posttraumatic Stress Disorder

Abstract: Peer support has been increasingly utilized within the Department of Veterans Affairs and offers an opportunity to augment existing care for posttraumatic stress disorder (PTSD). The current study sought to examine Veterans' perspectives on the potential benefits and drawbacks of peer support for PTSD. A sample of 23 Veterans with substantial treatment experience completed one-time qualitative interviews that were transcribed and coded for thematic content using grounded theory methodology. Results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 15 publications
4
84
0
Order By: Relevance
“…In a qualitative study of 23 veterans with PTSD, Hundt and colleagues found that veterans felt positively about peer-support interventions and anticipated benefits such as social support, normalization of symptoms, and increased initiation and adherence to adjuvant treatment. 58 Study participants expressed preference for peer-support groups segregated by specific trauma type and era of service, supporting the intent of our research to focus on post-9/11 veterans.…”
Section: Discussionsupporting
confidence: 61%
“…In a qualitative study of 23 veterans with PTSD, Hundt and colleagues found that veterans felt positively about peer-support interventions and anticipated benefits such as social support, normalization of symptoms, and increased initiation and adherence to adjuvant treatment. 58 Study participants expressed preference for peer-support groups segregated by specific trauma type and era of service, supporting the intent of our research to focus on post-9/11 veterans.…”
Section: Discussionsupporting
confidence: 61%
“…Along these lines of interpersonal connectedness and building on the core value of camaraderie articulated by veterans in this study, community-based interventions that incorporate veteran peers may be an important strategy to improve mental health outcomes. For example, research supports the unique benefits of veteran peer support specialists as an integrated component of treatment, with veterans reporting increased social and emotional support, stigma-reduction, and adherence (Hundt, Robinson, Arney, Stanley, & Cully, 2015). In addition, recent findings have indicated that veteran peer contact is associated with higher attendance and lower dropout during psychotherapy among a sample of 102 Post-9/11 treatment-seeking veterans (Goetter et al, 2018).…”
Section: Communication With Non-military Connected Personsmentioning
confidence: 97%
“…One systematic review expressed the need for additional research on the value of peer support on diabetes outcomes . Veterans have reported favourable experiences with peer‐support programmes , but less well known is the mechanics of how social support from peers helps veterans . Clinicians' experiences and perceptions of social support are rarely described, especially within the context of face‐to‐face group self‐management programmes.…”
Section: Introductionmentioning
confidence: 99%